Efectos del riego deficitario sobre el crecimiento y la producción de dos cultivares de Allium sativum L. en La Rioja (Argentina) = Effect of deficit irrigation on the growth and production of two cultivars of Allium sativum L. in La Rioja (Argentina) - Ibañez, Antonio; Carrizo, Jose Emilio (Asociación Argentina de Horticultura, 2024)
Horticulture in arid and semi-arid regions, as is the case in part of La Rioja, has several constraints, including water scarcity, high evaporation and hot, dry winds.Soil moisture, temperature and salinity were characterised and vegetative growth and bulb production were evaluated in two garlic cultivars under controlled deficit irrigation (from the main shoot growth stage until harvest) in western La Rioja. The trial was carried out at INTA EEA Chilecito. A factorial design of randomized treatments with four replications was used. Full irrigation (RC-100 % of ETc) was applied during the crop cycle and two levels with controlled deficit irrigation (RDC-75 % of ETc and RDC-50 % of ETc) from the 7th-10th visible leaf of the main growth stage 1 of leaf development (main shoot) until harvest in garlic cv. Morado INTA and cv. Nieve INTA. Gravimetric humidity (Hg), temperature and bulk soil electrical conductivity were measured. Leaf number, plant height and pseudostem, bulb diameter and bulb weight were measured. Results and Conclusions: From planting garlic until July, average values between 12 % Hg to 20 % Hg, between 30.2 ºC to 14.4 ºC of soil temperature and between 0.314mS.cm-1 to 0.090mS.cm-1 of bulk electrical conductivity were recorded. During water restriction, soil moisture and salinity decreased and soil temperature gradually increased. Deficit irrigation at 50 % ETc reduced bulb diameter and bulb weight. The application of deficit irrigation with 75 % ETc did not affect bulb diameter nor bulb weight. Garlic cv. Morado INTA exhibited higher leaf number and bulb weight. The application of controlled deficit irrigation, from the 7th-10th visible leaf of the main growth stage 1 of leaf development (main shoot) until harvest (01/08 to 24/11) in a western region of the province of La Rioja, differentially affects vegetative growth and bulb production, depending on the level of water restriction and garlic cultivar.